Field reports form for submitting seasonal observations of Iowa birds, Ed Thelen, fall 1998 - Thelen, Edet al (1998)
Fall report of birds found in northwestern Iowa contributed by Ed Thelen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed